Villenarchitektur am Semmering Semmering Architektur/ Band 2 - Buchinger, Günther (2006)
The present manuscript is intended to be part II of a publication in two volumes, but at the same time it can be seen as an independent, complete study. It deals with the different aspects of the historic architecture in the region of "Semmering" in southern Lower Austria. The book is the result of the FWF-project P 13959, in which one year of research under scientifically direction and supervision of the applicant (Prof. Dr. Mario Schwarz) was dedicated to intensive studies in art history, cultural history and history of architecture of this region. The author Dr. Guenther Buchinger - responsible collaborator of the project - attempted a large-scale research of the historical villas and county-houses at Semmering. The study contains a full, detailed documentation of the history and construction of the buildings and much information about the employers and the building contractors and architects as well. Consequently the author elaborated a comprehensive stylistic analyse. By the way of elucidating the circumstances of the construction of the buildings, it was possible to reconsider the background of the creating of this artificial settlement at Semmering. A certain social group of great influence among the Viennese bourgeoisie appears in this study, which created this recreation resort as a "vacation-paradise", at that time a complete new, futuristic project, motivated by personal and commercial interests likewise. The result, a colony of villas, was used not only for private purpose, but at the same time for tourism, partially in connection with the hotel buildings. In his stylistic analyse Guenther Buchinger gives a convincing proof that the phenomenon, which in general is subsumed as "homeland-style", "vernacular architecture" or "Swiss-cottage-style", in fact is a particular form of historicism between "severe historicism" and "late historicism". In the sense of "severe historicism" patterns of genuine architecture - by preference from publications on historical Swiss architecture - were used and extensively quoted. Consequently the forms and details developed in the style of "late historicism" in free evolution and eventually took into the formal repertory also elements of "Jugendstil". The scientific results of this study are important especially concerning the architects Franz von Neumann and Josef Buendsdorf, whose work has not yet been object of detailed research, but likewise for the general oeuvre of the prominent contractor's bureau Fellner & Helmer, whose theatre-architecture is already well documented in art history, but whose country houses and hotel-buildings are largely unknown. The study partially is designed as a catalogue, which presents each object in detail, and a comprehensive report of the scientific results in a distinct summary and contains numerous photos, plans and comparative illustrations.